BAND STRUCTURE, METALLIZATION AND STRUCTURAL PHASE TRANSITION OF NABR UNDER HIGHPRESSURE - Saminy, P.Penila; Ramola, Y.; Louis, C.Nirmala (International Journal of Engineering Technologies and Management Research, 2018)
The metallization and the phase transition of the alkali bromide sodium bromide (NaBr) is investigated through its band structure. The equilibrium lattice constant, bulk modulus, pressure derivative of bulk modulus and the phase transition pressure at which the compound undergo structural phase transition from NaCl (B1) to the CsCl (B2) structure is predicted from the total energy calculations. The ground state properties and band gap values are compared with the experimental and other theoretical results. At normal pressure NaBr is a direct band gap insulator. When the pressure is increased there is enhanced overlapping between the wave functions of the neighboring atoms. As a result the widths of the valence and empty conduction bands increase. These changes lead to the narrowing and indirect closing of band gap in NaBr (metallization). It is also confirmed that the metallization and structural phase transition do not occur simultaneously in ionic compounds.